Effect of balance valve on an asymmetric twin-scroll turbine for heavy-duty diesel engine. (July 2021) - Jin, Jianjiao; Pan, Jianfeng; Lu, Zhigang; Wu, Qingrui; Xu, Lizhong
A conventional asymmetric twin-scroll turbine with wastegate is capable of effectively tackling down the contradiction between fuel economy degradation and low nitrogen oxide emissions. However, as the engine speed has been rising at middle- and high-speed ranges, the pressure of small scroll inlet will be increasingly higher as compared with the intake pressure, thereby worsening fuel economy. In this study, a novel turbocharging technology of asymmetric twin-scroll turbine with a balance valve was first analyzed to more effectively balance the engine fuel economy and emission. The experiments on turbine test rig and engine performance were performed to explore the effects of balance valve on turbine performance, asymmetric ratio, exhaust gas recirculation rate, as well as engine performance. As the balance valve open degree was elevated, the turbine flow parameter was being extended, while the turbine efficiency was enhanced. Moreover, a lower asymmetric ratio could lead to a broader flow parameter range between that of partial admission and equal admission, thereby resulting in a broader regulating range of exhaust gas recirculation rate. In contrast with the asymmetric twin-scroll turbine with wastegate, the turbine running efficiency of asymmetric twin-scroll turbine with balance valve was enhanced by nearly 2%–11% at middle and high engine speed ranges, while the fuel economy was improved by nearly 1.5%–8%.